Physical Condition of Archery Athletes: Geographic and Demographic - Rizal, Rony Mohamad; Zuditya, Silvy; Hambali, Sumbara; Rizal, Yopi M (Universitas Suryakancana, 2023)
This study aimed to investigate the ability of the physical condition of PORPROV XIV athletes in archery in the KONI CIMAHI environment from demographic and geographical characteristics. The research method used was a quantitative descriptive method with a survey approach. The sample in the study was 16 athletes consisting of 8 female athletes and 8 male athletes with athlete characteristics in terms of gender, athlete age, domicile, and parental income. The sampling technique used is to use the saturated sample technique. Research instruments include yoyo tests to measure aspects of endurance; vertical jump test kits to measure limb power, to examine speed (speed) using a maximum speed of 30 meters and Sit and rich to examine flexibility. The results of this study are to have an average score of physical condition where athletes who are male (510.09), female (498.91), athletes living in rural areas (504.67), Urban (492.20), athletes with parental income of Rp. 71,200-Rp. 144,220 / day (517.81), >Rp.288,400 / day (516.32), Rp. 28,480-Rp. 56,960 / day (497.47), Rp. 158,620-Rp.288,400 / day (477.03), athletes aged 13-16 years (479.39), 17-20 (523.58), 17-24 (516.87), 28-30 (474.20). Thus, in this study, there is an average amount of different physical conditions of each KONI Cimahi archery athlete competing in the PorProv XIV West Java event in terms of gender, age, parental income, and domicile area.Â Keywords:Â Physical Condition, Archery, Age, Gender, Parental Income, Rural and Urban